Combined effects of okadaic acid and pectenotoxin-2, 13-desmethylspirolide C or yessotoxin in human intestinal Caco-2 cells. (August 2019) - Alarcan, Jimmy; Barbé, Sabrina; Kopp, Benjamin; Hessel-Pras, Stefanie; Braeuning, Albert; Lampen, Alfonso; Le Hégarat, Ludovic; Fessard, Valérie
Abstract: Lipophilic phycotoxins are secondary metabolites produced by phytoplanktonic species. They accumulate in filtering shellfish and can cause human intoxications. Humans can be exposed to combinations of several phycotoxins. The toxicological effects of phycotoxin mixtures on human health are largely unknown. Published data on phycotoxin co-exposure show that okadaic acid (OA) is simultaneously found with pectenetoxin-2 (PTX-2), 13-desmethylspirolide C (also known as SPX-1), or yessotoxin (YTX). Therefore, the aim of this study was to examine the effects of three binary mixtures, OA/PTX-2, OA/SPX-1 and OA/YTX on human intestinal Caco-2 cells. A multi-parametric approach for cytotoxicity determination was applied using a high-content analysis platform, including markers for cell viability, oxidative stress, inflammation, and DNA damage. Mixtures effects were analyzed using two additivity mathematical models. Our assays revealed that OA induced cytotoxicity, DNA strand breaks and interleukin 8 release. PTX-2 slightly induced DNA strand breaks, whereas SPX-1 and YTX did not affect the investigated endpoints. The combination of OA with another toxin resulted in reduced toxicity at low concentrations, suggesting antagonistic effects, but in increased effects at higher concentrations, suggesting additive or synergistic effects. Taken together, our results demonstrated that the cytotoxic effects of binary mixtures of lipophilic phycotoxins could not be predicted by additivity mathematical models. In conclusion, the present data suggest that combined effects of phycotoxins may occur which might have the potential to impact on risk assessment of these compounds. Highlights: OA is cytotoxic, triggers the release of IL-8 and induces DNA double-strand breaks in human intestinal cells. OA/PTX-2 mixture results in synergistic cytotoxicity at higher concentrations. Combination of another toxin to OA leads to antagonistic effects at low concentrations.